2015
DOI: 10.1007/s13197-015-1883-3
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic and antioxidant activity of Stevia rebaudiana extracts (Var. Morita) and their incorporation into a potential functional bread

Abstract: In this study a new wheat bread was designed whose sugars were replaced with S. rebaudiana Bertoni aqueous extract. The impact of the S. rebaudiana Bertoni aqueous extract on nutritional and sensory quality, its ability to reduce sugar intake and its antioxidant properties were investigated. Functional bread with 50 % of sugars replaced with S. rebaudiana extract was compared with traditional wheat bread. The extract demonstrated alpha amylase (IC 50 = 198.40 μg/mL) glucosidase (596.77 μg/mL) inhibition. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
37
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 28 publications
6
37
2
Order By: Relevance
“…In vivo and in vitro studies indicate that both stevia extract and stevioside have antihyperglycemic effects and their mechanisms of action are through gluconeogenesis suppression (stevia extract) and increased insulin secretion (stevia extract and stevioside); rebaudioside A increases insulin secretion exclusively in vitro and with high glucose concentrations (Aranda‐González, Segura‐Campos, Moguel‐Ordoñez, & Betancur‐Ancona, ). Other authors have stated similar results (Ruiz‐Ruiz et al, ).…”
Section: Pharmacokinetics Pharmacodynamics and Toxicologysupporting
confidence: 78%
See 2 more Smart Citations
“…In vivo and in vitro studies indicate that both stevia extract and stevioside have antihyperglycemic effects and their mechanisms of action are through gluconeogenesis suppression (stevia extract) and increased insulin secretion (stevia extract and stevioside); rebaudioside A increases insulin secretion exclusively in vitro and with high glucose concentrations (Aranda‐González, Segura‐Campos, Moguel‐Ordoñez, & Betancur‐Ancona, ). Other authors have stated similar results (Ruiz‐Ruiz et al, ).…”
Section: Pharmacokinetics Pharmacodynamics and Toxicologysupporting
confidence: 78%
“…Other studies showed similar antioxidant potentialities (Hajihashemi & Ehsanpour, 2014;Ruiz-Ruiz et al, 2015;Zayova, Stancheva, Geneva, Petrova, & Dimitrova, 2013). Vaško, Vašková, Fejerčáková, Mojžišová, and Poráčová (2014) reported that stevia has significant effects against hydroxyl radicals and has ability to decompose NO.…”
Section: Antioxidant Activitymentioning
confidence: 60%
See 1 more Smart Citation
“…Stevia leaves were ground in a grinding mill, and the resulting dried stevia leaf powder was sprayed in the mill with a 1‐mm mesh. Then, 500 mg of this powder were dispersed in 10 ml of water and incubated at 90°C for 5 min to obtain the AES, as previously reported (Ruiz‐Ruiz, Moguel‐Ordoñez, Matus‐Basto, & Segura‐Campos, ). Subsequently, AES was filtered through filter paper and cooled before administration to rats.…”
Section: Methodsmentioning
confidence: 99%
“…Inhibitors of these enzymes delay the breakdown of carbohydrates in the small intestine decreasing the absorption of glucose from starch and thereby diminishing the postprandial blood glucose excursion. These enzymes are important therapeutic targets for the modulation of postprandial hyperglycemia that is the earliest metabolic abnormality associated with type 2 diabetes mellitus (Ruiz-Ruiz et al 2015).…”
Section: Determination Of Antidiabetic Activitymentioning
confidence: 99%